2001
DOI: 10.1080/14622200110073380
|View full text |Cite
|
Sign up to set email alerts
|

The nicotinic antagonist methyllycaconitine has differential effects on nicotine self-administration and nicotine withdrawal in the rat

Abstract: Nicotinic acetylcholine receptor (nAChR) antagonists have been shown previously to decrease nicotine self-administration and precipitate elevations in brain reward thresholds and somatic signs of withdrawal in animals chronically exposed to nicotine. Both the positive-reinforcing effects of acute nicotine and the negative effects of nicotine withdrawal have been hypothesized to contribute to the development and maintenance of nicotine dependence. The aim of the present study was to use methyllycaconitine (MLA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 0 publications
8
111
0
2
Order By: Relevance
“…Nicotine-seeking behavior was observed to decrease when the function of the nicotine receptors and their related pathways were inhibited [29,30]. Thus, nicotine receptors are responsible for nicotine addiction.…”
Section: Discussionmentioning
confidence: 96%
“…Nicotine-seeking behavior was observed to decrease when the function of the nicotine receptors and their related pathways were inhibited [29,30]. Thus, nicotine receptors are responsible for nicotine addiction.…”
Section: Discussionmentioning
confidence: 96%
“…However, the α7-selective antagonist MLA did not change magnitude of nicotine-enhanced responding. Because the dose of MLA used in this study was the highest one or higher than the effective dose ever reported in literature (Gommans et al 2000;Grottick et al 2000;Markou and Paterson 2001), this single dose should not give rise to doubt on the lack of effect of this agent. Together, these data suggest that the nAChRs containing α4β2-but not α7-subunits may play an important role in mediating the reinforcement-enhancing effect of nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural findings are most readily explained by decreased number and/or function of nAChRs with the development of nicotine dependence that counteract the continuous agonist actions of nicotine on the receptors. Specifically, administration of a variety of nAChR antagonists induces withdrawal-like changes in rats exposed to nicotine at doses that have no effect in saline-treated subjects (Epping-Jordan et al 1998;Watkins et al 2000;Markou & Paterson 2001;Skjei & Markou 2003). Furthermore, different subtypes of nAChRs desensitize and upregulate at different rates, which may explain the seemingly opposite effects seen in some studies Buisson & Bertrand 2002;Levin 2002;.…”
Section: Neurosubstrates Of Nicotine Reward Dependence and Withdrawalmentioning
confidence: 99%
“…Such subjective positive effects support reliable intravenous nicotine self-administration behaviour in a variety of species, including rats, mice, non-human primates and humans (e.g. Markou & Paterson 2001; for a review, see Picciotto & Corrigall 2002). Persistent nicotine use leads to tolerance that is mediated by neuroadaptations occurring in response to chronic nicotine exposure.…”
Section: Behavioural Effects Of Acute Nicotine and Nicotine Withdrawalmentioning
confidence: 99%